Batasan Perlindungan Hukum Bagi Anak yang Dapat Dipertanggungjawabkan sebagai Pelaku Kejahatan - Hamdan, H.; Jaya, Alwi; Syam, Elvi Susanti (Fakultas Hukum, Universitas Muslim Indonesia, 2021)
This study aims to identify and understand the limits of legal protection for children who can be accounted for as criminals and to know and understand the factors that influence the consideration of legal protection for children who can be accounted for as criminals. This study uses a normative juridical approach. The analysis method is carried out by systematically identifying, polarizing, categorizing, and grouping according to the discussion flow in this study. Based on the description of the results and discussion, it can be concluded that the limitation of legal protection for children who can be accounted for as criminals, namely 12 years and under, children 12 years and over or under 14 years of age are subject to criminal sanctions in the form of action (action in the sense of juridical). Imprisonment is the last alternative for child perpetrators of crime, in contrast to adults. The factors that affect legal protection for children who can be held accountable as criminals are sociological and criminal aspects. The criminological aspect consists of three crucial sub-sectors, namely economy, environment, and family. Besides, regarding the concept of diversion, which has been sharpened with the concept of restorative justice, it is not time to become a constitutum in Indonesia because crimes in Indonesia are massive and systematic crimes.